Corporate Policies under Transitory and Permanent Shocks of Cash Flows: An Empirical Study of Cash Management - Saeed Bajalan; Reza MotaghianPour (تحقیقات مالی, 2021)
Objective: Theoretical corporate finance literature claims that financial policies of firms are related to the nature of their cash flows shocks; that is firms respond to transitory and permanent cash flow shocks differently. However, a limited number of surveys are conducted in the empirical corporate finance literature to verify the validation of these models.  The main objective of this article is to fill this gap. Methods: First of all, the existence of a permanent element in the cash flows of firms will be tested. Secondly, an adjusted filter will be devised to identify short term and permanent shocks to firms' cash flows and estimate their characteristics. This filter is adjusted according to the dynamics of this article's theoretical model. Eventually, the basic axioms of the dynamic framework on which the theoretical model is based, will be analyzed and then the hypotheses will be tested among sample classes. Results: 1- Modeling operational cash flows of companies as a combination of permanent and short-term stochastic processes can eliminate most of the problems assuming a permanent random process governing cash flows. 2- Pieces of evidence show that in firms that are operationally the same, the characteristics of permanent cash flows shock resemble. 3- While it is common to classifying stocks of companies whose sales are not affected by economic cycles as defensive industries, it seems that the separation of short-term and permanent shocks can provide a better criterion or distinguishing tool to interpreting this concept. 4- Firms that are exposed to higher cash flows volatility or experienced a greater permanent growth rate, hold a higher level of cash flows and at any time that they do external financing via equities, issue more stocks. Conclusion: According to the findings, separating short term and permanent shocks presents a strong intuition to describe firms' financial policies, and most implementations of the theoretical model of this article are acceptable.